An MMC-based cryogenic calorimeter with a massive sodium molybdate crystal absorber for neutrinoless double beta decay searches. (1st April 2022) - Kim, W.T.; Kim, S.C.; Sharma, B.; Grigorieva, V.D.; Jeon, J.A.; Kim, H.L.; Kim, H.J.; Kim, S.G.; Kim, S.R.; Kim, Y.D.; Kim, Y.H.; Lee, H.J.; et al.
Abstract: Sodium molybdate crystals are excellent scintillating target material that can be used to investigate the neutrinoless double beta decay of 100 Mo. Because this material contains Na nuclei, it could also be used to clarify the contribution of Na in the controversial claim of dark matter observation by the DAMA/LIBRA experiment. Recent developments have allowed the growth of sodium molybdate crystals of several hundred grams, which makes it possible to build large scale experiments. Therefore, a cryogenic calorimeter with a crystal of significant mass, which can exploit the excellent energy resolution from thermal signals and particle identification using the scintillation signals, is highly desired. We have developed a cryogenic calorimeter with a cylindrical sodium molybdate crystal of 178 g with dimensions of 4 cm (height) × 4 cm (diameter) coupled to a metallic magnetic calorimeter (MMC). The detector was also equipped with a light detector with a thin Ge absorber to detect scintillation signals. The detector test measurements showed excellent energy resolution and particle discrimination using dual detection of heat and light signals, and thus demonstrate that the crystal is a promising tool for searching for rare phenomena events. Details of the detector development with the massive sodium molybdate crystal are discussed in this paper along with the performance results from test measurements.